MAIN TYPES OF VIOLENT BEHAVIOR IN THE CONTEMPORARY SOCIETY - MARIA LULESCU (Challenges of the Knowledge Society)
The proposed scientific theme is going to approach and study the violence phenomenon as a contemporary social matter, from a conceptual and etiological perspective. Firstly, the violence phenomenon is explained from multiple angles: legal, psychological, socio – political, anthropological and last but not least sociological ones. Secondly, I am going to analyze the main violence types encounted in contemporary society; this approach also implies the study of the way each violence type is expressed, and the discovery of the causes that determine the commission of such acts. Thirdly, the main types of violence existing in sport are presented, this phenomenon being frequently encounted in contemporary society, while converting a sport game into a real battle – a situation which is frequent both among athletes and especially supporters.